NATO needs deterrence and dialogue : defining the new balance in view of the Warsaw summit - Major, Claudia (2016)
Zusammenfassung: Deterrence is back in Europe. As NATO approaches its July summit in Warsaw, Allies are adapting this concept to the new security settings in place in Europe since the 2014 crisis in Ukraine. Yet, deterrence is intrinsically connected to dialogue: these are the two pillars of NATO's strategy, as defined in the 1967 Harmel Report. Consequently, in a security environment in which Russia uses military force to coerce neighbours and violates international law by redrawing borders, NATO needs to find a new balance between deterrence and dialogue to safeguard security in Europe. NATO rightly is strengthening its deterrence measures as an urgent priority for Alliance security. These steps should be framed as part of a double-track strategy that, over time, will encourage Russia to abide by international norms - not through blandishments, but through transatlantic unity and strength. This will require sustained political commitment, backed up by military and diplomatic resources. Germany and the US should lead within NATO the development of a durable new balance of deterrence and dialogue that will sustain Alliance cohesion and establish conditions for lasting peace in Europe. (SWP Comments)